Clinical Legal Education and its Implication on Legal Education System in Pakistan: Challenges and Prospects - Rashida Zahoor; Naureen Akhtar; Rao Imran Habib (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2021)
Purpose: To improve the standard of legal education, legal clinic is one of the modern techniques. Legal profession is a noble profession as it is considered to uphold the justice in a society. A law student may be taught in a such manner that he must be well equipped with professional skills. Methodology: Previous studies have been discussed with the help of current data for thorough review of challenges in Pakistan.  Findings: In Pakistan, legal education system needs many reforms in order to produce good lawyers. Without professional skills and practical knowledge; a law graduate is unable to utilize his degree in a proper manner. To attain such professional skills; legal clinics are good approach. Where students may be able to seek practical knowledge and also helping the deserving people. LL. B degree awarding institutions shall make it possible to provide clinical legal education. Law clinics must be installed in law faculties where the experts may be available to educate students. Implications: In this paper, the importance of law clinic is discussed and certain issues are highlighted which are prevailing in current legal education system of Pakistan. Study can help out policy makers to identify challenges and to overcome these issues they can formulate different strategies.